Demographic compensation occurs in populations of Quercus oleoides Schltdl & Cham in fragments across an altitudinal gradient - Flores-Romero, Carlos; Sánchez-Velásquez, Lázaro Rafael; Equihua, Miguel; Pineda López, María del Rosario; Alarcón Gutiérrez, Enrique; Perroni, Yareni (PeerJ, 2025)
Background Demographic compensation is a complex process by which populations can compensate for the effects of anthropogenic disturbance and other environmental changes and restore growth-rate stability (λ » 1). Dynamic equilibrium is achieved when the growth rate [λ] is close to one. This enables a population to persist under changing environmental conditions. The demographics of fragmented populations provides an ideal model to explore the processes by which populations adapt through demographic compensation responses. Aims To characterize the demographic of Quercus oleoides populations and detect the various processes that result from demographic compensation responses. Methods We established permanent plots in three Q. oleoides populations at which three annual transition stages were registered. These were survival probability, transition probability, and average reproduction (that is, the number of seed production by size class). Results The λs of the three populations under study were >1.0 (P < 0.005). However, differences were found in the elasticity matrices, as well as in the life-table response experiment (LTRE) variation analyses. Conclusions The three Q. oleoides populations have shown to have affected a transition to demographic compensation and achieved demographic balance through different strategies in their vital rates.
Keywords: Autoregulation; Demography; Elasticity matrix; LTRE variation; Mexico; Oak; Population dynamic; Population growth rate